Pengaruh Citra Merek Dan Promosi Terhadap Keputusan Pembelian Pada Aplikasi Platform E- Commerce Shopee (Studi Pada Konsumen Shopee: Mahasiswa Unuja) - Kulsum, Ummi; Fahrudin (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2025)
This study aims to analyze in depth the influence of brand image and promotion on purchase decisions on the Shopee e-commerce platform, focusing on Nurul Jadid University students. The background of the research is based on the rapid growth of e-commerce in Indonesia and the increasing competitiveness between digital platforms, where brand image and promotion are strategic factors in influencing consumers. The approach used is quantitative associative with the survey method through the distribution of online questionnaires. The research population was 4,762 students with a sample of 369 respondents, using the proportionate stratified random sampling technique. The research instruments were tested for validity and reliability with satisfactory results (r-count > r-table and Cronbach's Alpha > 0.7). Data analysis was carried out using multiple linear regression, F test, t test, and classical assumption test. The results showed that brand image and promotion simultaneously had a significant effect on purchasing decisions (F-count = 158,132; Sig = 0.000). Partially, brand image had a positive effect with a regression coefficient value of 0.337 (t-count = 6.674), while promotion had a significant effect with a regression coefficient of 0.283 (t-count = 8.736). The value of the determination coefficient (R²) of 0.464 indicates that 46.4% of the variation in purchasing decisions can be explained by both variables, while the rest is influenced by other factors. These findings confirm the power of a positive brand image, combined with innovative promotional strategies such as discounts, free shipping, interactive campaigns, and the use of influencers, to encourage consumers, especially students, to make purchasing decisions. The practical implications of this study indicate that Shopee and other digital business actors need to strengthen positive brand perceptions and increase the effectiveness of promotions to win competition in the digital era.